Pengaruh IPM, Investasi, dan UMP terhadap Tingkat Pengangguran Terbuka di Jawa Timur Tahun 2013-2020 - Lailatul Qamariyah; Olga Mardianita W.P; Sulistya Rusgianto (OECONOMICUS Journal of Economics, 2022)
Economic development is an effort to improve people's living standards through expanding job opportunities and directing the distribution of income evenly. However, in reality there are still many problems that occur, especially in unemployment. The purpose of this study was to determine the effect of the variable Human Development Index, Investment, and Provincial Minimum Wage on the open unemployment rate in East Java in 2013-2020. The method used in this study is a quantitative method with multiple linear regression analysis model. The data used are secondary data obtained from BPS. This study shows that the HDI and Investment variables have a positive influence on the open unemployment rate. However, the UMP variable has a negative effect on the open unemployment rate in East Java in 2013-2020. This study contributes to the existing literature that it is not always the HDI, Investment, and UMP variables that can affect the open unemployment rate which can hinder economic growth.